Small animal irradiator dose distribution verification using radioluminescence imaging. Issue 7 (7th April 2020) - Spinelli, Antonello E.; D'Agostino, Emilano; Broggi, Sara; Claudio, Fiorino; Boschi, Federico
Abstract: The main objective of this work was the development of a novel 2D dosimetry approach for small animal external radiotherapy using radioluminescence imaging (RLI) with a commercial complementary metal oxide semiconductor detector. Measurements of RLI were performed on the small animal image‐guided platform SmART, RLI data were corrected for perspective distortion using Matlab. Four irradiation fields were tested and the planar 2D dose distributions and dose profiles were compared against dose calculations performed with a Monte Carlo based treatment planning system and gafchromic film. System linearity and RLI image noise against dose were also measured. The maximum difference between beam size measured with RLI and nominal beam size was less than 8% for all the tested beams. The image correction procedure was able to reduce perspective distortion. A novel RLI approach for quality assurance of a small animal irradiator was presented and tested. Results are in agreement with MC dose calculations and gafchromic film measurements. Abstract : In this work we developed of a novel 2D dosimetry approach for small animal external radiotherapy using radioluminescence imaging (RLI). Different irradiation fields were tested and 2D dose distributions and dose profiles were compared against dose calculations performed with a Monte Carlo (MC) based treatment planning system and gafchromic film. System linearity and RLI image noise against dose were also measured. Results are in agreement with MC dose calculations and gafchromic film measurements.